Three-dimensional printed surfaces inspired by bi-Gaussian stratified plateaus - Hu,S; Cao,X; Reddyhoff,T; Puhan,D; Huang,W; Shi,X; Peng,Z; Dini,D (ACS Applied Materials and Interfaces, 2019)
Wettability of artificial surfaces is attracting increasing attention for its relevant technological applications. Functional performance is often achieved by mimicking the topographical structures found in natural flora and fauna; however, surface attributes inspired by geological landscapes have so far escaped attention. We reproduced a stratified morphology of plateaus with a bi-Gaussian height distribution using a three-dimensional direct laser lithography. The plateau-inspired artificial surface exhibits a hydrophobic behavior even if fabricated from a hydrophilic material, giving rise to a new wetting mechanism that divides the well-known macroscopic Wenzel and Cassie states into four substates. We have also successfully applied the plateau-inspired structure to droplet manipulation.